Penerapan Model Kooperatif Tipe Make A Match untuk Meningkatkan Literasi Sains dan Hasil Belajar Siswa - Sahmanita, Riqqah Salsabila; Hanifah, Nurdinah; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2019)
This research is based on result of study observation it caused by study application mode which is not accordance with its implementation which is effect into a low completed student learning outcomes, in order to resolve this problems the researcher takes an alternative solution using the implementation of cooperative model Make A Match type. The aims on this research to describe how to plan and apply a learning to improve ability of scientific literacy and learning outcomes of VA students in SDN Pasanggrahan I as a research sample. This research is being done on three cycles, cycle I show that student ability of scientific literacy is 56,50%, cycle II 73,91%, and cycle III 91,30%. So the student learning outcomes looks improve at the cycle I reach 73,91%, cycle II 82,60%, and cycle III 91,30%. The conclusion is the implementation of cooperative model Make A Match type can improve the scientific literacy and student learning outcomes.